Validation of the Parent-Adolescent Communication Scale among University Students from Lima - Araujo-Robles, Elizabeth Dany (2018)
The purpose of this study was to provide evidence of validity and reliability for the Barnes and Olson’s (1982) Parent-Adolescent Communication Scale among university students from Lima, aged 16 to 25. Participants were 255 students (162 females) from two universities. An exploratory factor analysis was performed to assess the viability of bi-factor and tri-factor structures. This exploratory factor analysis supported the two-factor structure originally proposed for this instrument (open communication and problem communication). Both in the father-adolescent and in the mother-adolescent version, obtained Cronbach’s alpha values were high (ranging between .80 and .90). The structural model also showed good fit indexes. This confirms the reliability and validity of this instrument in the sample under study.